Training, hypnosis, and drugs: artificial synaesthesia, or artificial paradises? - DEROY, Ophelia; Spence, Charles (Frontiers in Psychology, 2013)
The last few years have seen the publication of a number of studies by researchers claiming to have induced “synaesthesia”, “pseudo-synaesthesia”, or “synaesthesia-like” phenomena in non-synaesthetic participants. Although the intention of these studies has been to try and shed light on the way in which synaesthesia might have been acquired in developmental synaesthestes, we argue that they may only have documented a phenomenon that has elsewhere been accounted for in terms of the acquisition of sensory associations and is not evidently linked to synaesthesia. As synaesthesia remains largely defined in terms of the involuntary elicitation of conscious concurrents, we suggest that the theoretical rapprochement with synaesthesia (in any of its guises) is unnecessary, and potentially distracting. It might therefore be less confusing if researchers were to avoid referring to synaesthesia when characterizing cases that lack robust evidence of a conscious manifestation. Even in the case of those other conditions for which conscious experiences are better evidenced, when training has been occurred during hypnotic suggestion, or when it has been combined with drugs, we argue that not every conscious manifestation should necessarily be counted as synaesthetic. Finally, we stress that cases of associative learning are unlikely to shed light on two highly specific characteristic of developmental synaesthesia in terms of learning patterns: First, their resistance to change through exposure ; Second, the transfer of conditioned responses between concurrents and inducers after training. We conclude by questioning whether, in adulthood, it is ever possible to acquire the kind of synaesthesia that is typically documented in the developmental form of the condition. The available evidence instead seems to point to there being a critical period for the acquisition of synaesthesia, probably only in those with a genetic disposition to develop the condition.